Study of LV functions in patients of subclinical hypothyroidism in patients coming to rural medical college of Sub-Himalayan region of India - Kumar, Pankaj; Singh, Narinder; Kapoor, Dhiraj; Dogra, Varun Deep; Kumar, Rupinder; Agarwal, Vishnu Kumar; Kumar, Manoj; Shoeb, Ansari Mohd (International Journal of Research in Medical Sciences, 2017)
Background:Subclinical hypothyroidism (SCH) is a common disorder and has been implicated in increased cardiovascular morbidity and mortality. Therefore, it is important to study the effect of SCH on cardiac morphology and function. Thus, present study titled “Study of LV functions in patients of subclinical hypothyroidism in patients coming to rural medical of sub-Himalayan region of India” was conducted in the department of medicine, Rajinder Prasad government medical Tanda over a period of three years from December, 2010 to November, 2013 to study left ventricular function in subclinical hypothyroidism. Methods: The study was conducted in the department of medicine, Rajinder Prasad government medical Tanda over a period of three years from December, 2010 to November, 2013 to study left ventricular function in subclinical hypothyroidism. The data was analysed using computer software Epi-info version 6.0 and SPSS version 12.0 for Windows. Descriptive characteristics were presented as percentages for quantitative variables including measurement of thyroid hormones and ejection fraction. Mean and standard deviation were reported. Results:Diastolic parameters were markedly altered, mainly isovolumic relaxation time, which was increased and reduction of E/A wave ratio (<1). Systolic function parameters were within normal range. 155 patients had diastolic dysfunction with E/A wave <1.45 patients were not affected and they had E/A wave >1. Conclusions:Implication for echocardiography in SCH patients observed were that early recognition of silent diastolic dysfunction can be done. We can institute L-thyroxinee therapy which has been found to reverse diastolic dysfunction of heart along with improvement in lipid levels, decreased systemic vascular resistance, diastolic hypertension and coagulation profile. SCH, invariably affects heart and sooner or later and leads to diastolic dysfunction. Early recognition by echocardiography and then treatment with L-thyroxinee is indicated.